InnB, a Novel Type III Effector of Bradyrhizobium elkanii USDA61, Controls Symbiosis With Vigna Species - Nguyen, Hien P.; Ratu, Safirah T. N.; Yasuda, Michiko; Göttfert, Michael; Okazaki, Shin (Frontiers in Microbiology, 2018)
Bradyrhizobium elkanii USDA61 is incompatible with mung bean (Vigna radiata cv. KPS1) and soybean (Glycine max cv. BARC2) and unable to nodulate either plant. This incompatibility is due to the presence of a functional type III secretion system (T3SS) that translocates effector protein into host cells. We previously identified five genes in B. elkanii that are responsible for its incompatibility with KPS1 plants. Among them, a novel gene designated as innB exhibited some characteristics associated with the T3SS and was found to be responsible for the restriction of nodulation on KPS1. In the present study, we further characterized innB by analysis of gene expression, protein secretion, and symbiotic phenotypes. The innB gene was found to encode a hypothetical protein that is highly conserved among T3SS-harboring rhizobia. Similar to other rhizobial T3SS-associated genes, the expression of innB was dependent on plant flavonoids and a transcriptional regulator TtsI. The InnB protein was secreted via the T3SS and was not essential for secretion of other nodulation outer proteins. In addition, T3SS-dependent translocation of InnB into nodule cells was confirmed by an adenylate cyclase assay. According to inoculation tests using several Vigna species, InnB promoted nodulation of at least one V. mungo cultivar. These results indicate that innB encodes a novel type III effector controlling symbiosis with Vigna species.